Evolução, desvios e tensões na formação de uma infraestrutura de informação: estudo de caso do sistema integrado de gestão da Universidade Federal do Rio Grande do Norte - Silva, Larrissa Dantas Xavier da (2021)
The objective of this research is to study, from the theoretical perspective of information infrastructures (II), the evolution, deviations and socio-technical tensions in the formation of the Integrated Management System (IMS) of the Federal University of Rio Grande do Norte, with significant use in the area of Brazilian higher education. The research is based on an exploratory qualitative strategy, using the case study as a method. The methods for data collection were three: collection of documents, interviews and questionnaires. For the stage of selection, analysis and interpretation of the data, a framework was developed that was based on the theoretical foundations of the II and its objective is to systematize the analysis of the results. The research was carried out at the Federal University of Rio Grande do Norte and at the Federal University of Paraíba. The arrival of IMS in the Brazilian higher education sector dynamically assists in the collaboration between the organization, teachers, students and civil servants, promoting speed in internal processes and decision making. As a result of this research, it will be possible to identify the process of how the evolution, the tensions and deviations suffered by the IMS took place, helping the development team and actors responsible for the organizational sector to consider what is being positive and negative in this process. It is concluded that the systems were the result of a succession of tensions and deviations, hence their emergent and continuous character. Such tensions and deviations were not limitations to its evolution. The IMS has been continuously built incrementally with each evaluation cycle and has the infrastructure role of articulating different communities of practice.